Challenging Islamophobia by Action (An Overview of the Islamic Activist Movement in America from A Fiqh Aqalliyāt Perspective) - Khalik, Subehan; Hj Rofie, Mohamad Khadafi; Usman, Ummi Farhah; Nur Wulan Rohimah (Jurnal Adabiyah, 2024)
The issue of Islamophobia and the treatment of minorities is deeply rooted in the culture of Muslim societies. Throughout history, Islamic constitutional law has focused on the treatment of minority groups. However, the meaning of "minority" has evolved and shifted from referring to non-Muslim minority groups to Muslim minority groups. This research employs a qualitative methodology with an Islamic law and legal sociology approach, relying on empirical data. The article aims to emphasize the need for reassessing "minorities" and setting new standards in combating Islamophobia through a sociological approach by advocating fiqh al-Aqalliyāt as a tool to promote inclusivity among the Muslim majority. The results show that the movement against Islamophobia, based on the study of maqashid al-shariah with an emphasis on fiqh al-aqalliyat, is the main choice for American Muslim minorities. Abstrak Isu Islamofobia dan perlakuan terhadap minoritas berakar kuat dalam budaya masyarakat Muslim. Sepanjang sejarah, hukum konstitusional Islam telah berfokus pada perlakuan terhadap kelompok minoritas. Namun, makna "minoritas" telah berevolusi dan bergeser dari merujuk pada kelompok minoritas non-Muslim menjadi kelompok minoritas Muslim. Penelitian ini menggunakan metodologi kualitatif dengan pendekatan hukum Islam dan sosiologi hukum, dengan mengandalkan data empiris. Artikel ini bertujuan untuk menekankan perlunya menilai kembali "minoritas" dan menetapkan standar baru dalam memerangi Islamofobia melalui pendekatan sosiologis dengan mengadvokasi fiqh al-Aqalliyāt sebagai alat untuk mempromosikan inklusivitas di antara mayoritas Muslim. Hasil penelitian menunjukkan bahwa gerakan melawan Islamofobia yang didasarkan pada kajian maqashid al-syariah dengan penekanan pada fiqh al-aqalliyat menjadi pilihan utama bagi minoritas Muslim Amerika.